High-resolution infrared study of AsH2D: The stretching fundamental bands ν1/ν5 and ν2; Journal of Molecular Spectroscopy; Vol. 252, iss. 1 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Yukhnik (Yuhnik) Yu. B. Yuliya Borisovna; Vershinina O. G.; Jerzembec W.; Burger H. (2008, 2008)
Title screen